Misdiagnosed High-Grade Undifferentiated Sarcoma Mimicking Infantile Myofibroma: A Case Report. - Bhanvadia, Soham; Risch, Mary Jane; Goncalves, Luis; Desai, Sudhen (Applied Radiology, 2026)
Accurate prenatal diagnosis of fetal masses is challenging due to their varied presentation and the limitations of current imaging modalities, which are typically restricted to obstetric US and non-contrast fetal MRI. We present a case involving a right forearm mass first identified on prenatal US and MRI, which initially appeared benign and was diagnosed as infantile myofibroma following excisional biopsy. However, due to rapid growth and persistent symptoms, the patient ultimately underwent transhumeral amputation, with final pathology revealing a high-grade undifferentiated sarcoma. This case highlights the diagnostic complexity of fetal soft tissue tumors and underscores the importance of maintaining a broad differential, including malignancy, even when imaging and initial pathology suggest a benign process.